Clinical Manifestation and Molecular Characterization of a Novel Member of the Nannizziopsiaceae in a Pulmonary Granuloma From a Galapagos Tortoise (Chelonoidis nigra) - Christman, Jane E.; Alexander, Amy B.; Donnelly, Kyle A.; Ossiboff, Robert J.; Stacy, Nicole I.; Richardson, Rebecca L.; Case, J. Brad; Childress, April L.; Wellehan, James F. X. (Frontiers in Veterinary Science, 2020)
Nannizziopsiaceae is a family of fungal organisms within the order Onygenales containing two genera of important reptile pathogens, Nannizziopsis and Paranannizziopsis. A captive Galapagos tortoise (Chelonoidis nigra) from Boca Raton, Florida, United States, was presented for a clinical history of chronic progressive lethargy and inappetence. At initial presentation, the tortoise had a moderate nonregenerative anemia, leukocytosis, whip-like heterophil projections, erythrocyte fragmentation, and fibrin strands, with the latter two raising concern for disseminated intravascular coagulation. A single large encapsulated pulmonary granuloma was identified through imaging, including plain film radiography and bronchoscopy. Direct intralesional samples were obtained from transcarapacial celioscopy for fungal culture, cytology, histopathology, and polymerase chain reaction. Amplification and sequencing of the ITS2 region of the rRNA genes with Bayesian and maximum likelihood analyses placed the fungus in the family Nannizziopsiaceae within the order Onygenales, representing a novel fungal species.